Outcomes of patients with fludarabine-refractory chronic lymphocytic leukemia: a population-based study from a well-defined geographic region. Issue 8 (August 2014) - Eketorp Sylvan, Sandra; Hansson, Lotta; Karlsson, Claes; Norin, Stefan; Lundin, Jeanette; Österborg, Anders
Abstract Patients with fludarabine-refractory (FR) chronic lymphocytic leukemia (CLL) receive novel agents in pivotal, non-randomised phase-2 trials. Understanding outcome of FR-CLL in health-care may provide important contextual information. Records from 1301 patients (Stockholm-Cancer-Registry 1991–2010) identified 92 FR-patients; bulky lymph-nodes (BFR-group), double-refractory (DR-group), or Others'-group for outcome-analysis. Median age was 69 years 67% had Rai-stage III/IV with median 3 prior therapies. Overall response-rate was 20%; significantly lower in BFR (8%, p = 0.01) and DR (20%, p = 0.01) than in 'Others' (31%). Time-to-treatment-failure (months) was significantly longer in 'Others' (9.2) than in BFR/DR (5.3/4.4) (p < 0.01) and significantly longer (p < 0.05) in antibody-treated patients (9.1) compared to other regimens (5.2). Early-death occurred in 5%, ≥ grade III-infections in 20%. Median overall-survival (OS) was 18 months; 29 in BFR vs 13 in DR (p = 0.054). Male sex was the only prognostic factor on OS (p = 0.01, HR 2.2, multivariate-Cox-regression). Our results, without external referrals, facilitate interpretation of non-randomised trials/novel drugs in advanced-stage-CLL.